Ex libris inż. Wojciech Krzyżak [Irena Nowakowska-Acedańska]. - Nowakowska-Acedańska, Irena (1906-1983) (s.n., 1946)
Kaloryfer, fragm. rury wodociągowej, zakończonej kranem z płynącą wodą; w tle budynki.